O Padre Cícero nas narrativas e nas práticas pedagógicas docentes em Juazeiro do Norte – Ceará: perspectivas para o diálogo inter-religioso - Castro, Rogério Paiva (2018)
The objective of this dissertation was to understand the process of constructing ideas and beliefs about Father Cícero from the narratives of the religious experience of nine teachers from the municipal public education network of Juazeiro do Norte - Ceará, and then analyze how these repercussions on pedagogical practices, whether or not they contribute to interreligious dialogue. The curricular subjects focused were Regional Studies and Religious Education, taught in the final years of Elementary School. It was a qualitative research (BOGDAN and BICKLEN, 1994), based on the theoretical-methodological contributions of (self)biographical research in education (JOSSO, 2007, 2010); (Delory-Momberger, 2008, 2012, 2014). The narratives of the teachers were woven into the research and training device called Biographical Reflective Circle (OLINDA, 2010) and were interpreted in the hermeneutic circle proposed by Moraes (2003), entitled Discursive Textual Analysis. The entire process was accompanied by the roaming log technique (BARBIER, 2007). As for Father Cícero, the work is essentially based on Dumoulin (2017). Both the narratives and the didactic-pedagogical treatment around this controversial public figure reflect contradictions, incomprehensions and impasses that hinder interreligious dialogue, treated in the present work in the perspective of human rights and the process of spiritualization of being (TEIXEIRA, 2003, 2014); (WOLFF, 2014); (PANIKKAR, 2007). The need for investments in teacher training and improvement / deepening in the processes of teaching and learning was evident. The myth Father Cícero needs to be problematized, giving rise to the priest and politician who left significant examples on the paths to be followed by a church that respects the popular faith and commits itself to the reversion of cadres of subalternization and social inequalities. There is still much to be done in the sense of greater openness to pedagogical practices that contribute to interreligious dialogue and, consequently, to the construction of social peace in the context of religions.